(3EOGQI GdehGO h GdLhOI GdTGedI (B/s - (3GdWGgQ, YdGA aQLs ((3YeGf(B: s (3OGQ GdQGjI(B, s, 2007)
(3eaGgje EOGQjI CSGSjI , GdGJUGd eY GdYedGA GdeQJbHjf , EOGQI GdefTBJ GdUfGYjI h GdeNRhf GdSdYj LQO GdeRGO h GdQbGHI Ydi GdeNRhf , EOGQI GdehGOh Sdhc GdeSJgdc GdaQOj , eNJUQGJ h eUWdMGJ GdGSJjQGO h GdJUOjQ , EOGQI GdehGO h GdefGhdI , EOGQIGdehGO h GdTQGA , GOGQI GdLhOI cfXGe h GdGHYGO GdGSJQGJjLjI dGOGQI GdLhOI ,feGPL Yf GOGQI GdLhOI GdTGedI, GOGQI GddhGRe(B.s
(3eQGLY U(B.183s
Keywords: (3GdCYeGd `` GOGQIs; (3GdGfJGL `` GOGQIs; (3GdEfJGL GdUfGYjs; (3GdehGO `` GOGQIs; (3VHW GdLhOIs